Case Report: Upper gastrointestinal bleeding and multiorgan injury caused by ethylicin poisoning - Hu, Wensi; Li, Tongyao; Du, Yu; Yang, Mingyang; Liu, Si; He, Songbai; Long, Qian; Fan, Xing; Zhou, Zinan; Li, Xiaoyuan; Liu, Junzhao (Frontiers in Pharmacology, 2024)
Ethylicin is a pesticide with excellent bactericidal ability. The incidence of poisoning has increased in recent years with the widespread use of ethylicin in green agriculture, but reports are lacking. In this study, we described three cases of oral ethylicin poisoning. Patients developed severe upper gastrointestinal bleeding after oral administration of ethylicin. Gastroscopy showed extensive mucosal erosions and ulcerations in the esophagus, stomach, and duodenum. Impaired consciousness, multiorgan injury, irreversible shock, and cardiac arrest were observed in cases where larger doses of ethylicin were ingested. Patients were treated with comprehensive therapeutic measures, including total gastrointestinal decontamination, medications such as proton pump inhibitors and somatostatin to reduce gastric bleeding. Endoscopic hemostasis was performed when pharmacologic hemostasis was not effective.Parenteral nutritional support and organ function support were given. In patients' follow up, esophageal stenosis and dysphagia during feeding was noted, which severely affected the quality of life. Ethylicin poisoning has been a public health problem and the awareness should be raised.